THE IMPACT OF DETENTION AND ARREST ON THE PRESUMPTION OF INNOCENCE IN THE CONTEXT OF EUROPEAN COURT JUDGMENTS - Khalilov Yunis Farman; Mirzazade Yusif Emin (World Scientific Reports, 2024)
The article is dedicated to examining the impact of "detention" and "imprisonment" on the presumption of innocence in the context of the decisions made by the European Court of Human Rights. The article analyzes detention and imprisonment from the perspective of the presumption of innocence, specifically addressing how exceeding the "reasonable time" affects this principle. According to the authors, when applying detention or imprisonment that restricts an individual's freedom before the final court decision, the presumption of innocence is fully applicable, provided that the requirements of Article 5 of the European Convention on Human Rights are strictly followed. The authors also believe that exceeding the "reasonable time" can be seen as an additional punishment beyond the expected sentence. Therefore, special attention should be paid to ensuring that the "reasonable time" does not extend beyond the potential length of the imposed sentence.